Reimagining the purpose of VET - expanding the capability to aspire in South African Further Education and Training students - Powell, Lesley (Elsevier, 2012)
This paper applies the capabilities approach to the broader debate of the role of vocational education and training (VET) in poverty alleviation. The capabilities approach provides an approach for conceptualising and evaluating VET which differs in orientation from dominant productivist conceptions. It does so by shifting the focus from economic development to human development. By placing the well-being of VET students at the centre of our concern it shifts the lens from income generation and with it employability to a lens on capability expansion which includes but is not limited to the capability to work. The paper is based on interviews with 20 South African Further Education and Training (FET) college students. The central argument is that VET has an important role to play in poverty alleviation, but only if located in a multi-dimensional view of poverty which understands poverty as capability deprivation across multiple human functionings. In this broader notion of poverty, the role that VET plays includes training for employability, but also includes the expansion of other important capabilities such as, and in the voice of a FET student interviewed in this study, ‘the ability to dream’, or in the language of the capabilities approach, the capability to aspire.